THE ANALYSIS OF VIOLATING MAXIM ON SAPA INDONESIA MALAM TELEVISION NEWS PROGRAM TOWARD THE EPISODE ‘TUDINGAN KONSPIRASI DIBALIK KORONA’ - Atika Wati; Indra Nabilah Zahra (Program Studi Pendidikan Bahasa Inggris Fakultas Keguruan dan Ilmu Pendidikan, 2020)
When interacting with other people, we must cooperate during the conversation. By cooperating, it will make the conversation run well and flow smoothly. However, the speaker can violate the maxim and caused understanding. This study aims to analyze violating maxims done by a speaker on ‘‘Sapa Indonesia Malam” news program that consists of two segments. The writers analyze the data by applying the theory of cooperative principle by Grice and using descriptive qualitative method. The result of this study showed that there are sixty-four violating utterances. Relation maxim comes as the most common maxim that violating by the speaker. It occurs twenty-eight times during the conversation. After that, it was followed by quality maxim with twenty-one violation utterances. Then ten times of violation quantity maxim and maxim of manner as the lowest violation because it only occurs five times.